New models in geography : the political-economy perspective. - Peet, Richard, 1940-; Thrift, N. J. (Unwin Hyman, 1989)
Two decades after the publication of the seminal Models in Geography, edited by Richard Chorley & Peter Haggett, this major collection of specially commissioned essays charts the new human geography from the perspective of political economy.